"Discourse is heavy, fasting": Food Imagery in Titus Andronicus and Cymbeline. (2nd October 2019) - Paravano, Cristina
ABSTRACT: This essay explores how Shakespeare developed his re-envisioning of the myth of the Roman empire and its civilization through recourse to food images in Titus Andronicus and Cymbeline . Both plays are punctuated by references to foodstuffs, animals and mutilated body parts, while at the same time featuring moments of conviviality. Within the conventions of different genres, Shakespeare exploited such elaborate food imagery to discuss, from a specular perspective, the same issues, while simultaneously conveying his vision of Rome. In Titus Andronicus the recurring bodily parts are the epitome of the fragmentation of the body politic of "headless Rome" (1.1.186) and of the disintegration of the traditional Roman values and principles under the threat of barbaric invasion. On the other hand, in Cymbeline, set at the time of Emperor Augustus, Shakespeare seems to take stock of his previous works, many of which powerfully resonate in this play, shaping an ambiguous and fascinating image of Rome.